PENGEMBANGAN MODEL PEMBELAJARAN VCT (VALUE CLARIFICATION TECHNIQUE) BERBASIS TPACK UNTUK MENINGKATKAN MORAL DAN BUDAYA SISWA - Chandra, Shinta Gress; Sutrisna Wibawa; Insanul Qisti Barriyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The background for conducting this research is the existence of children's moral decadence which is characterized by widespread issues regarding cases of moral deviation involving children. In cases that often occur in schools, a lack of moral understanding makes children easily commit violence against their own friends. Apart from that, other things such as being rude to teachers and cheating, are also other examples of moral problems. For this reason, we need a way to overcome children's moral problems, so that it is hoped that these problems will no longer occur. One of them is by implementing learning using the VCT (Value Clarification Technique) method based on TPACK (Technological, Pedagogical And Content Knowledge) to improve students' moral reasoning in Civics learning in elementary schools. The research was carried out at SD Negeri CR, with the research subjects being 27 students in sixth grade (20 boys, 7 girls). Data analysis techniques use tests and documentation. The results of this research indicate that the use of the TPACK-based VCT method improves students' moral value reasoning. Proven by an increase in learning outcomes in 2 cycles. The second cycle showed an increase in Learning Completeness to 24 children, from only 10 children previously. With this increase in the level of learning completeness, it can be concluded that the VCT method has a positive impact on students' moral reasoning in thematic learning PKn and SBdP in sixth grade of elementary school.